2017
DOI: 10.4162/nrp.2017.11.4.290
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein-1 polymorphism interaction with spirulina immunomodulatory effects in healthy Korean elderly: A 16 week, double-blind randomized clinical trial

Abstract: BACKGROUND/OBJECTIVESSpirulina is a known a functional food related to lipid profiles, immune functions, and antioxidant capacity. Circulating monocyte chemoattractant protein-1 (MCP-1) level is associated with inflammation markers. Single nucleotide polymorphism in the MCP-1 promoter region -2518 have been identified and shown to affect gene transcription. Gene variation may also impact functional food supplementary effects. The current study investigated the interaction of MCP-1 -2518 polymorphism with spiru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…At first, significant increasing effect on IL‐2 concentrations was observed following spirulina supplementation (SMD = 2.69 pg/mL; 95% CI: 0.26, 5.11; P = .03) according to our analysis on seven arms of clinical trials (Figure 3A), however, the results were insignificant (SMD = 0.54 pg/mL; 95% CI: −1.29, 2.27; P > .05) after removing Park (2017) study 31 because of its large and heterogenic effect size. Remarkable heterogeneity was observed between studies ( P < .001, I 2 = 97.6%).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…At first, significant increasing effect on IL‐2 concentrations was observed following spirulina supplementation (SMD = 2.69 pg/mL; 95% CI: 0.26, 5.11; P = .03) according to our analysis on seven arms of clinical trials (Figure 3A), however, the results were insignificant (SMD = 0.54 pg/mL; 95% CI: −1.29, 2.27; P > .05) after removing Park (2017) study 31 because of its large and heterogenic effect size. Remarkable heterogeneity was observed between studies ( P < .001, I 2 = 97.6%).…”
Section: Resultsmentioning
confidence: 70%
“…Subjects with various health conditions were involved in included studies. Two studies involved hypertensive patients, 22,23 one study recruited patients with allergic rhinitis, 24 one study enrolled diabetic patients 25 and the other studies investigated the effect of spirulina supplementation on healthy subjects 10,26‐31 . Furthermore, location of studies execution were as follows: four in Korea, 10,25,29,31 one in California, 24 one in Mexico, 23 one in Poland, 22 one in Greece, 30 one in Iran, 28 one in Brazil, 26 and one in Taiwan 27 …”
Section: Resultsmentioning
confidence: 99%
“…The results make it easier to develop customized diet plans that help the immune system work better [32].…”
Section: Immunostimulation Effects Of Spirulinamentioning
confidence: 99%
“…The Spirulina supplement changes how the MCP‐1 genotype reveals inflammation. The results make it easier to develop customized diet plans that help the immune system work better [32].…”
Section: Health Aids Of Spirulinamentioning
confidence: 99%
“…Other research has demonstrated that Spirulina can enhance innate immunity in mice and inhibit tumor growth by modulating the balance between interleukin (IL)-17/IL-23 and interferon (IFN)-γ ( 11 ). An investigation in elderly Korean participants found that Spirulina supplementation may influence the expression of inflammatory markers like IL-2 and tumor necrosis factor (TNF)-α through monocyte chemotactic protein-1 (MCP-1), suggesting that Spirulina is useful for improving immune function ( 12 ). Spirulina has also been widely applied to patients with human immunodeficiency virus (HIV).…”
Section: Introductionmentioning
confidence: 99%